PMMA-augmented SI screw: a biomechanical analysis of stiffness and pull-out force in a matched paired human cadaveric model. (October 2015) - Grechenig, Stephan; Gänsslen, Axel; Gueorguiev, Boyko; Berner, Arne; Müller, Michael; Nerlich, Michael; Schmitz, Paul
Abstract: Introduction: Current literature data and clinical experience show that the number of pelvic fractures continuously rises due to the increasing elderly population. In the elderly with suspected osteoporosis additional implant augmentation with bone cement seems to be an option to avoid secondary displacement. There are no reported biomechanical data in the literature comparing the fixation strength (and anchorage) of standard and augmented SI screws so far. The purpose of this study was to assess the biomechanical performance of cement-augmented versus non-augmented SI screws in a human cadaveric pelvis model. Material and Methods: Six human cadaveric pelvises preserved with the method of Thiel were used in this study. Each pelvis was split to a pair of 2 hemi-pelvises, assigned to 2 different groups for instrumentation with one non-augmented or one contralateral cement-augmented SI screw, placed in the body of S1 in a randomized fashion. The osteosynthesis followed a standard procedure with 3D controlled percutaneous iliosacral screw positioning. A biomechanical setup for a quasistatic pullout test of each SI screw was used. Construct stiffness and maximum pullout force were calculated from the load-displacement curve of the machine data. Statistical evaluation was performed at a level of significance p = .05 for all statistical tests. Results: Stiffness and pullout force in the augmented group (501.6 N/mm ± 123.7, 1336.8 N ± 221.1) were significantly higher than in the non-augmented one (289.7 N/mm ± 97.1, 597.7 N ± 115.5), p = .04 and p = .014, respectively. BMD influenced significantly the pullout force in all study groups. Conclusion: Cement augmentation significantly increased the fixation strength in iliosacral screw osteosynthesis of the sacrum in a biomechanical human cadaveric model.